(untitled) - Seymour Lipschutz (New York, 1997)
The book presents a modern elementary introduction to linear algebra. The first part of the book deals with vectors and matrices, and systems of linear equations. This leads naturally to the topics of vector spaces and subspaces, and to the formal definition of linear dependence and independence, and dimension. Next comes on inner product spaces; linear mapping; and the relationship between linear transformations and matrices. The chapter on eigenvalues and eigenvectors and the diagonalization of linear operators is preceded by a chapter on determinats. The final chapter deals with quadratic forms
Keywords: algebras, linear - outlines, syllabi, etc,algebras, linear - problems, exercises, etc